Soveršenstvovanie techniki bar'ernogo bega u junošej s kvalifikaciej tret'ego i vtorogo razrjada na distancii 400 metrov s bar'erami - Bugay, M. V.; Getman, S. A.; Osipov, S. V.; Skripnikov, P. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Hurdle running refers to the athletics exercises, the effective implementation of which, among other factors, depends on the existing coordination abilities of the athlete. They largely determine the technique of movements, which in this case is of paramount importance, since it is impossible to achieve the significant result in hurdling without perfection in overcoming each barrier, naturally while maintaining the highest possible speed. However, in the practice of training young hurdlers, the development of the specific coordination abilities, characteristic for this sport event, the implementation of which contributes to the formation of technique, is not always taken into account. This circumstance requires the certain approach to solving this problem.